Aspek Hukum Kontrak Bagi Hasil (Production Sharing Contract) dalam Pengusahaan Pertambangan Minyak dan Gas Bumi di Indonesia - Haris Retno Sumiyati (Fakultas Hukum Universitas Mulawarman, 2006)
Oil and Natural Gas Mining is strategic commodity which become one of the Indonesian earnings pledge. According to ability of state, there are various model of mining effort, one of mining effort called Production Sharing Contract on Oil and Natural Gas Mining. Production Sharing Contract is important on Oil and Natural Gas Mining, because according to Undang-undang Nomor 22 Tahun 2001 tentang Minyak dan Gas Bumi, every Oil and Natural Gas Mining must be conducted by an executive body based on cooperation contract. Even if there is Oil and Natural Gas Mining done without cooperation contract with executive body can be told as illegal mining and punishable. Key words: kontrak (contract); kontrak bagi hasil (production sharing contract), pertambangan (mining); minyak (oil); gas bumi (natural gas)